YKL‐40‐gene polymorphism affects acute cellular rejection and fibrosis progression after transplantation for hepatitis C virus‐induced liver disease. Issue 1 (19th December 2012) - Eurich, Dennis; Neumann, Ulf P; Boas‐Knoop, Sabine; Neuhaus, Ruth; Kiessling, Anja; Yahyazadeh, Ali; Trautwein, Christian; Wasmuth, Hermann; Puhl, Gero; Neuhaus, Peter; Bahra, Marcus
Abstract Background and Aim The development of end‐stage graft disease is suspected to be partially determined by an individual genetic background. The aim of our study was to determine the prevalence of YKL‐40‐gene polymorphism in hepatitis C virus (HCV)‐positive patients and its impact on the incidence of acute cellular rejection (ACR), graft fibrosis and antiviral treatment response. Methods A total of 149 patients, who underwent liver transplantation for HCV‐induced liver disease, were genotyped for YKL‐40 (rs4950928; G/C) by TaqMan Genotyping Assay. The results were correlated with 616 post‐transplant graft biopsies regarding inflammation, fibrosis and evidence for ACR. Results No association of YKL‐40‐gemotypes was observed regarding mean inflammation grade (P = 0.216) and antiviral treatment outcome (P = 0.733). However, the development of advanced fibrosis (F3‐4) was significantly faster in patients with YKL‐40‐G‐allele: t(CC) = 4.6 versus t(CG/GG) = 2.4 years; P = 0.006. Patients with lower fibrosis (F0‐2) compared to advanced fibrosis (F3‐4) received significantly more frequent dual immunosuppression (calcineurin inhibitors [CNIs]/mofetile mycophenolate [MMF] vs CNIs; P = 0.003). ACR‐occurrence was associated with YKL‐40‐genotypes (ACR: CC = 60.4%, CG = 25.0% and GG = 14.6% vs non‐ACR: CC = 74.2%, CG = 23.8% and GG = 2.0%; P = 0.009) and with gender compatibility between donor and recipient (P = 0.012). Conclusion Fibrosis progression and ACR‐incidence after transplantation for HCV‐induced liver disease seem to be under genetic control. The negative impact of G‐allele on post‐transplant events observed in our study, deserves attention and should be verified in larger liver transplantation‐cohorts.